The Impact of Workplace Health Promotion Programs Emphasizing Individual Responsibility on Weight Stigma and Discrimination - Täuber, Susanne; Mulder, Laetitia B.; Flint, Stuart W. (Frontiers in Psychology, 2018)
Over time, there has been a steady increase of workplace health promotion programs that aim to promote employees’ health and fitness. Previous research has focused on such program’s effectiveness, cost-savings, and barriers to engaging in workplace health promotion. The present research focuses on a downside of workplace health promotion programs that to date has not been examined before, namely the possibility that they, due to a focus on individual responsibility for one’s health, inadvertently facilitate stigmatization and discrimination of people with overweight in the workplace. Study 1 shows that the presence of workplace health promotion programs is associated with increased attributions of weight controllability. Study 2 experimentally demonstrates that workplace health promotion programs emphasizing individual rather than organizational responsibility elicit weight stigma. Study 3, which was pre-registered, showed that workplace health promotion programs emphasizing individual responsibility induced weight-based discrimination in the context of promotion decisions in the workplace. Moreover, focusing on people with obesity who frequently experience weight stigma and discrimination, Study 3 showed that workplace health promotion programs highlighting individual responsibility induced employees with obesity to feel individually responsible for their health, but at the same time made them perceive weight as less controllable. Together, our research identifies workplace health promotion programs as potent catalysts of weight stigma and weight-based discrimination, especially when they emphasize individual responsibility for health outcomes. As such, we offer valuable insights for organizations who aim to design and implement workplace health promotion programs in an inclusive, non-discriminatory way that benefits all employees.